2016
DOI: 10.1128/aem.03398-15
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and Anaerobic Thiosulfate Oxidation by a Cold-Adapted, Subglacial Chemoautotroph

Abstract: T he comminution of bedrock in subglacial systems promotes weathering processes by exposing fresh minerals with a high surface area (1-5). Subglacial water chemical profiles (e.g., see references 5 and 6), field-and laboratory-based microcosm experiments (e.g., see references 7-9), and molecular analyses (e.g., see references 6, 10, and 11) indicate the presence of an active and diverse subglacial microbiome founded on chemical energy that functions to enhance rates of mineral weathering (8). Given that ice co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Further evidence for lithotrophic primary production in subglacial sediments includes the recovery of RuBisCO mRNA transcripts (Boyd et al, 2014) and the isolation of Thiobacillus sp. RG5 (a member of the Betaproteobacteria subphyla) from subglacial sediments in the Canadian Rockies (Harrold et al, 2016). In polar and subpolar regions, chemolithoautotrophic activity can fix several micrograms of carbon per m 2 per day (Gaidos et al, 2004;Mikucki and Priscu, 2007;Christner et al, 2014).…”
Section: Subglacial Zonementioning
confidence: 99%
“…Further evidence for lithotrophic primary production in subglacial sediments includes the recovery of RuBisCO mRNA transcripts (Boyd et al, 2014) and the isolation of Thiobacillus sp. RG5 (a member of the Betaproteobacteria subphyla) from subglacial sediments in the Canadian Rockies (Harrold et al, 2016). In polar and subpolar regions, chemolithoautotrophic activity can fix several micrograms of carbon per m 2 per day (Gaidos et al, 2004;Mikucki and Priscu, 2007;Christner et al, 2014).…”
Section: Subglacial Zonementioning
confidence: 99%
“…Overridden soils and vegetation are a potentially important source of DOM along the southwestern margin of the GrIS, where the margin of the ice sheet retreated back from its current position during the Holocene Thermal Maximum (Lecavalier et al, ; Levy et al, ). Alternative subglacial sources to overridden soils and vegetation might include lithogenic DOM (Petsch et al, ; Petsch et al, ), chemolithoautotrophic production of DOM (Birdwell & Engel, ; Chen et al, ; Harrold et al, ), and the reworking of existing DOM by subglacial microbial communities (Cameron et al, ; Lamarche‐Gagnon et al, ; Stibal et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thiobacillus sp. are traditionally known as sulfur oxidizing microorganisms (SOMs) and have been found in polar environments previously (Boyd et al, 2014; Purcell et al, 2014; Harrold et al, 2016); however, it has also been suggested that certain Thiobacillus species carry out reverse dissimilatory sulfite reduction (rDsr, or reverse dsr) as an alternative means to oxidize reduced sulfur compounds (Loy et al, 2009; Purcell et al, 2014). This could well be an alternative pathway that is present in the BFP system; however, it would require transcriptomic evidence to confirm its activity.…”
Section: Discussionmentioning
confidence: 99%